Inhibition of SARS-CoV-2 growth in the lungs of mice by a peptide-conjugated morpholino oligomer targeting viral RNA - Alexandra Sakai; Gagandeep Singh; Mahsa Khoshbakht; Scott Bittner; Christiane V. Löhr; Randy Diaz-Tapia; Prajakta Warang; Kris White; Luke Le Luo; Blanton Tolbert; Mario Blanco; Amy Chow; et al. (Elsevier, 2024)
Further development of direct-acting antiviral agents against human SARS-CoV-2 infections remains a public health priority. Here, we report that an antisense peptide-conjugated morpholino oligomer (PPMO) named 5'END-2, targeting a highly conserved sequence in the 5' UTR of SARS-CoV-2 genomic RNA, potently suppressed SARS-CoV-2 growth in vitro and in vivo. In HeLa-ACE 2 cells, 5'END-2 produced IC50 values of between 40 nM and 1.15 μM in challenges using six genetically disparate strains of SARS-CoV-2, including JN.1. In vivo, using K18-hACE2 mice and the WA-1/2020 virus isolate, two doses of 5'END-2 at 10 mg/kg, administered intranasally on the day before and the day after infection, produced approximately 1.4 log10 virus titer reduction in lung tissue at 3 days post-infection. Under a similar dosing schedule, intratracheal administration of 1.0-2.0 mg/kg 5'END-2 produced over 3.5 log10 virus growth suppression in mouse lungs. Electrophoretic mobility shift assays characterized specific binding of 5'END-2 to its complementary target RNA. Furthermore, using reporter constructs containing SARS-CoV-2 5' UTR leader sequence, in an in-cell system, we observed that 5'END-2 could interfere with translation in a sequence-specific manner. The results demonstrate that direct pulmonary delivery of 5'END-2 PPMO is a promising antiviral strategy against SARS-CoV-2 infections and warrants further development.